Field evaluation of root rot disease and relationship between disease severity and yield in cassava - Onyeka, T.J.; Dixon, Alfred G.O.; Ekpo, E.J.A. (Cambridge University Press, 2005)
eports of cassava root rot disease from different African countries have increased in recent times. Field studies were conducted from July 1998 to October 1999 to determine a reproducible disease assessment method that would allow the comparison of results from different locations and an evaluation of the relationship between disease severity and root yield. Single point disease assessments at 6, 9, 12 and 15 months after planting (MAP) were compared to multiple points assessment based on the area under a disease progress curve (AUDPC). Single point assessments at 12 and 15 MAP, and the AUDPC identified continuous variation (p≤0.01) among the genotypes. However, a consistent result across trials was obtained only with the assessment based on AUDPC. Root dry yield (DYLD) at 15 MAP showed a strong negative correlation with AUDPC (r=−0.74). Regression analysis also confirmed the negative relationship between yield and root rot severity. The five genotypes compared were separated into resistant (91/02324, 30572 and 92/0427) and susceptible (92/0057 and TME-1) groups. It was concluded that root rot disease may cause significant yield loss; however, the magnitude of the yield loss will depend on the susceptibility of the cassava genotype.